Armaments and ornaments: mate-guarding and the evolutionary roots of religion - Czachesz, István (Religion, brain & behavior, 2020)
This article explores the connection between sexual selection and religion, locating the origins of religious behavior in mate guarding after the transition to terrestrial life in Homo erectus 1.8 million years ago. An important consequence of the transition was the emergence of a polygynous, multiple-family social structure, which gave rise to mate guarding as a successful strategy. Further, as a result of sleeping on the ground, REM (rapid-eye-movement) phases were substantially extended. This produced novel dream experiences in Homo erectus, which is identified as the origin of proto-religious traits. The article argues that proto-religious dream experiences and related behavioral expressions gave males psychological and strategic advantages in keeping competitors away from their females. Given the strong selective pressure of male competition in polygynous mating systems, biological traits underlying proto-religion were successful in natural selection. Finally, it is suggested how subsequent evolutionary leaps in human cognition shaped religious thought and behavior and their role in sexual selection. The article is concluded by outlining how elements of the mate-guarding hypothesis could be tested and improved using empirical methods.